El agregado de Hordeum murinum (Poaceae) en “Flora Iberica”. - León, Eduardo; López Nieto, Eusebio; López Martínez, Mónica; Pujadas Salvá, Antonio J. (Acta Botanica Malacitana, 2014)
Hordeum murinum aggregate in “Flora iberica” Palabras clave. Hordeum, Poaceae, corología, taxonomía, Hordeae. Key words. Hordeum, Poaceae, chorology, taxonomy, Hordeae.